(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease and it is characterized by selective death of upper and lower motor neurons causing muscle atrophy, weakness and spasticity. As it is a fatal neurodegenerative disease, we can slow down the progression of symptoms through treatment. The present report deals with a case of ALS which can be correlated to Kapha avrutha vyana vata. Current paper is a case report of 47 year old female patient presented with the complaints of weakness and wasting of bilateral lower limb (Rt>Lt) since 20 years and weakness of bilateral upper limb (Rt>Lt) since 10 years and was diagnosed with progressive ALS. Aim of the study is to introduce an alternative therapeutic modality through Ayurveda which help to improve quality of life and delay the progress of disease. Patient had been treated with specific Panchakarma treatment modalities - Udwarthana, Acchasnehapana, Kukkudanda pinda sweda, Kayaseka, Mamsa pinda sweda, Musthadi Rajayapana vasti and specific Samana and Rasayana oushadis. The response of the patient’s condition to the treatment was assessed by ALSFRS -R Score. A substantial decrease in the intensity of symptoms was observed with a better quality of day to day activities. Thus, the treatment was found to be effective in managing the present ailment.